Age and growth estimates for the nurse shark (Ginglymostoma cirratum) over 17 years in Bimini, The Bahamas - Fadool, Baylie A.; Bostick, Kylie G.; Brewster, Lauran R.; Hansell, Alexander C.; Carlson, John K.; Smukall, Matthew J. (Frontiers in Marine Science, 2024)
Age and growth estimates are essential for life history modeling in elasmobranchs and are used to inform accurate conservation and management decisions. The nurse shark (Ginglymostoma cirratum) is abundant in coastal waters of the Atlantic Ocean, yet many aspects of their life history remain relatively understudied, aside from their reproductive behavior. We used mark-recapture data of 91 individual G. cirratum from Bimini, The Bahamas, from 2003 to 2020, to calculate von Bertalanffy (vB) growth parameters, empirical growth rate, and age derived from the resulting length-at-age estimates. The Fabens method for estimating growth from mark-recapture methods was applied through a Bayesian framework using Markov chain Monte Carlo (MCMC) methods. This provided growth parameters with an asymptotic total length (L∞) of 303.28 cm and a growth coefficient (k) of 0.04 yr-1. The average growth rate for G. cirratum was approximately 8.68 ± 6.00 cm yr-1. This study also suggests that the previous maximum age for G. cirratum is likely underestimated, with the oldest individual predicted to be 43 years old. Our study is the first to present vB growth parameters and a growth curve for G. cirratum. It indicates that this species is slow-growing and long-lived, which improves our understanding of their life history.